THE ROLE OF SONGS AND SINGING IN THE EVERYDAY PRACTICES OF THE UPA AND OUN SOLDIERS IN ZAKERZONNIA - PROKOPOV, Vadym (EAST EUROPEAN HISTORICAL BULLETIN, 2025)
The purpose of the research is to elucidate and characterize the everyday military practices related to singing and the use of music among the UPA and OUN soldiers in Zakerzonnia region in 1944 – 1947. Research Methodology. The study is based on an interdisciplinary approach that combines the analysis of memoir sources and insurgent documents with theoretical developments in military anthropology, social psychology, and musicology. In the research musicological approaches and concepts have been applied that explain the role of a collective singing in shaping group identity and in combat situations. Scientific Novelty. This article represents the first attempt to explore the anthropological dimension of the use of songs and singing in daily lives of the UPA and OUN soldiers in Zakerzonnia. The research expands the understanding of musical practices in military environments and opens new perspectives for studying the impact of a song on the psychological state and combat effectiveness of military formations. Conclusions. Thus, the role of a song and singing in everyday practices of the UPA and OUN soldiers in Zakerzonnia was multidimensional. The analysis of the sources shows that music served not only an entertainment or emotional function but also acted as a powerful tool for psychological adaptation, group identification, and even tactical influence on the enemy. This study identifies the functions that singing and songs played in the daily lives of the Ukrainian combatants. In particular, singing and songs served as a means of rest and leisure; accompaniment for celebrations and rituals; a tool for unity and communication; emotional support and stress relief; a marker of national identity and the distinction between “us” and “them”; an instrument of ideological influence and propaganda; support in combat situations; and the final act before death. Collective singing contributed to the formation of group identity and the maintenance of morale. Singing practices united combatants and civilians, becoming a kind of ritual that strengthened camaraderie and mutual understanding. Singing played a crucial role in regulating emotional states, alleviating anxiety, and improving mood. The article argues that the phenomenon of “combat singing” was used as a means of influencing the enemy. By analyzing these aspects, we not only gain a deeper understanding of the psychology and culture of the Ukrainian underground but also acquire a broader perspective on the role of music in military conflicts in general. Key words: Ukrainian Insurgent Army, Organization of Ukrainian Nationalists, Zakerzonnia, combat singing, everyday life, military anthropology.